2006
DOI: 10.1580/pr43-05.1
|View full text |Cite
|
Sign up to set email alerts
|

Variables Contributing to Acute Mountain Sickness on the Summit of Mt Whitney☆

Abstract: Objective.-The interaction of 15 variables representing physical characteristics, previous altitude exposure, and ascent data was analyzed to determine their contribution to acute mountain sickness (AMS).Methods.-Questionnaires were obtained from 359 volunteers upon reaching the summit of Mt Whitney (4419 m). Heart rate and arterial oxygen saturation were measured with a pulse oximeter, and AMS was identified by Lake Louise Self-Assessment scoring. Multiple logistic regression analysis was used to identify sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 31 publications
5
29
0
1
Order By: Relevance
“…Supporting this hypothesis are several reports of people with impaired cerebrospinal buffering capacity due to space-occupying lesions, who have developed symptoms of raised ICP when exposed either to altitude32 33 or to the hypobaric hypoxia of commercial aircraft 34. Conversely, there is a lower incidence of AMS in older people,35 who have been shown to have a greater CSF-to-brain volume 36. In our study, the three subjects with ONSD >6 mm at 5200 m all had increases in the region of 1.5 mm compared with sea level.…”
Section: Discussionmentioning
confidence: 92%
“…Supporting this hypothesis are several reports of people with impaired cerebrospinal buffering capacity due to space-occupying lesions, who have developed symptoms of raised ICP when exposed either to altitude32 33 or to the hypobaric hypoxia of commercial aircraft 34. Conversely, there is a lower incidence of AMS in older people,35 who have been shown to have a greater CSF-to-brain volume 36. In our study, the three subjects with ONSD >6 mm at 5200 m all had increases in the region of 1.5 mm compared with sea level.…”
Section: Discussionmentioning
confidence: 92%
“…There appears to be no association between SpO 2 and AMS when the pulse oximetry measurement is taken soon after arriving at high altitude. 5,6 However, several researchers have suggested that low SpO 2 might be a predictor of impending AMS if the climber remains at altitude or continues a prolonged ascent. 7,8 Could finger pulse oximetry also be used to predict summit success or failure for an ascent of a high altitude peak?…”
Section: Introductionmentioning
confidence: 99%
“…5,16,17 However, it should also be noted that Gautret and colleagues found that older travelers are more likely to consult a physician about serious altitude illness than younger travelers, whereas Leshem and colleagues found that older climbers were more likely to be evacuated for pulmonary edema than young climbers. 6,18 Perhaps older travelers are less prone to altitude illness but when they do become ill they do not recover as quickly and thus have to be hospitalized more often.…”
Section: Predictorsmentioning
confidence: 99%